The Arts Interview. Commissions of Government, Part 1 : Peter Bell - Memorial University of Newfoundland. Division of Educational Technology (Memorial University of Newfoundland. Division of Educational Technology, 1985)
Host Fred Hollingshurst interviews artist Peter Bell, who discusses the creation of the large mural he was commissioned to do for the Confederation Building in St. John's, Newfoundland. His technique is described and demonstrated in part.